Glycogen synthase kinase‐3 controls IL‐10 expression in CD4+ effector T‐cell subsets through epigenetic modification of the IL‐10 promoter. Issue 4 (17th February 2015) - Hill, Elaine V.; Ng, T. H. Sky; Burton, Bronwen R.; Oakley, Charly M.; Malik, Karim; Wraith, David C.
<x xml:space="preserve">Abstract</x> The serine/threonine kinase glycogen synthase kinase‐3 (GSK3) plays an important role in balancing pro‐ and anti‐inflammatory cytokines. We have examined the role of GSK3 in production of IL‐10 by subsets of CD4+ T helper cells. Treatment of naive murine CD4+ T cells with GSK3 inhibitors did not affect their production of IL‐10. However, treatment of Th1 and Th2 cells with GSK3 inhibitors dramatically increased production of IL‐10. GSK3 inhibition also led to upregulation of IL‐10 among Th1, Th2, and Th17 subsets isolated from human blood. The encephalitogenic potential of GSK3 inhibitor treated murine Th1 cells was significantly reduced in adoptive transfer experiments by an IL‐10‐dependent mechanism. Analysis of the murine IL‐10 promoter in response to inhibition of GSK3 in Th1 cells showed modification to a transcriptionally active state indicated by changes in histone H3 acetylation and methylation. Additionally, GSK3 inhibition increased expression of the transcription factors c‐Maf, Nfil3, and GATA3, correlating with the increase in IL‐10. These findings are important in the context of autoimmune disease since they show that it is possible to reprogram disease‐causing cells through GSK3 inhibition.